Qualitative Data Sharing: Participant Understanding, Motivation, and Consent. (January 2022) - VandeVusse, Alicia; Mueller, Jennifer; Karcher, Sebastian
Expectations to share data underlying studies are increasing, but research on how participants, particularly those in qualitative research, respond to requests for data sharing is limited. We studied research participants' willingness to, understanding of, and motivations for data sharing. As part of a larger qualitative study on abortion reporting, we conducted interviews with 64 cisgender women in two states in early 2020 and asked for consent to share de-identified data. At the end of interviews, we asked participants to reflect on their motivations for agreeing or declining to share their data. The vast majority of respondents consented to data sharing and reported that helping others was a primary motivation for agreeing to share their data. However, a substantial number of participants showed a limited understanding of the concept of "data sharing." Additional research is needed on how to improve participants' understanding of data sharing and thus ensure fully informed consent.